PERCEPTION OF WOMEN OF REPRODUCTIVE AGE TOWARDS LONG-ACTING CONTRACEPTIVE (LAC) COUNSELING OF FAMILY PLANNING COUNSELORS: A QUALITATIVE STUDY - Asdawati, Asdawati; Bachtiar, Adang (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Long-acting contraceptive (LAC) is one kind of birth control method for preventing, spacing pregnancy or stopping the fertility for an extended period. Increasing the number of LAC user can be done by providing a good quality of LAC counseling. This study aims to explore the perception of reproductive woman in LAC counseling by family planning counselors. Methods: This study was a qualitative study with Rapid Assessment Procedure (RAP) design. This study conducted in Bontomatene, Selayar Island on April 2019. There were 6 samples that represent 3 samples used LAC and 3 samples used non-LAC. The in-depth interview was used to get the information and the interactive model analysis was used in analyzed the data. Results: 5 of 6 respondents mentioned when the family planning counselor explained LAC used native language was easier to understand. The counseling by family planning counselor was already good because the counselor explained in detail information about LAC, visited the house of respondents to give information and did not push the respondents to select contraceptive methods. Conclusions: The reproductive woman in Bontomatene, Selayar Island feel more comfortable with LAC counseling held by family planning counselor if using native language, explain in detail information and not force respondent to use LAC methods.